Antara Pengampunan Dosa Islam dan Hindu: Menuju Konsep Berwudhu’ dan Mandi di Sungai Gangga Sebagai Media Penyucian Diri : A Comparative Study of Sin Forgiveness in Islam And Hinduism: Wudu’ and Ganges Bathing as Means of Purification - Najiyah, Nur Laili Nabilah Nazahah (El-Suffah: Jurnal Studi Islam, 2025)
Islam and Hinduism share similar concepts of sin forgiveness in various respects, one of which is the use of purification materials as a means of repentance before God. Thus, this article aims to address two main research questions: What are the concepts of sin forgiveness in Islam and Hinduism? And how are the practices of wudu’ and ritual bathing in the Ganges River understood within each tradition? Primary data is derived from the holy scriptures of Islam and Hinduism, as well as from literature specifically related to the practices of wudu’ (ritual purification-taharah) and ritual bathing in the Ganges River. Secondary data is collected from books, academic journals, and official websites relevant to the research theme. The analysis employs a comparative method to examine purification practices in Islam and Hinduism. The findings reveal that, first, sin forgiveness in Islam is termed taubah (repentance), which involves sincere intention, remorse, and the effort to engage in righteous deeds. In Hinduism, the corresponding concept is known as prayascitta, which is performed through samskara ceremonies, signifying physical purification, although the essence of purification is ultimately spiritual. Second, in Islam, wudu’—when performed with the intention of repentance and seeking forgiveness for sins committed through various body parts—results in both physical and spiritual purification. Meanwhile, in Hinduism, ritual bathing in the Ganges River is believed to cleanse individuals of sins, bringing about forgiveness and salvation. These two practices indicate that both Islam and Hinduism regard sacred water as essential for purification from bodily sins. Moreover, both traditions emphasize the importance of intention in seeking forgiveness, aiming to restore both the physical and spiritual purity of the individual. Abstrak: Islam dan Hindu memiliki konsep pengampunan dosa yang mirip dari beberapa aspek, salah satunya yakni material penyucian diri sebagai upaya bertaubat kepada Tuhan. Oleh karenanya, artikel ini bertujuan menjawab dua rumusan masalah: bagaimana konsep pengampunan dosa dalam Islam dan Hindu; serta bagaimana konsep berwudhu’ dan ritual mandi di Sungai Gangga. Data primer diperoleh dari kitab suci umat Islam dan Hindu, serta literatur terkait persoalan wudhu’ (thaharah) dan ritual mandi di Sungai Gangga pada khususnya. Sementara data sekundernya dari buku, jurnal, maupun situs resmi berkaitan dengan tema penelitian. Analisis dilakukan dengan metode komparasi untuk menarik konklusi atas material penyucian diri dalam Islam dan Hindu. Hasilnya, Pertama, pengampunan dosa dalam Islam dikenal dengan istilah taubat yang dilaksanakan dengan hati tulus, penyesalan dan berusaha berbuat kebajikan. Sementara dalam Hindu, dikenal dengan sebutan prayascita melalui upacara samskara, yakni penyucian diri secara jasmani. Meskipun, penyucian diri yang utama adalah secara batin. Kedua, wudhu’ yang didasari niat bertaubat dan memohon ampunan atas dosa anggota tubuhnya kepada Allah swt, maka jasmani dan batinnya akan kembali bersih.  Sedangkan dalam Hindu, melakukan ritual mandi di sungai Gangga dipercaya dapat membersihkan dosa-dosa pada diri manusia dan memperoleh ampunan serta keselamatan. Kedua hal ini memberikan pemahaman bahwa Islam dan Hindu sama-sama membutuhkan air (suci), yang dapat mensucikan diri dari dosa-dosa bagian anggota tubuh.  Selain itu, keduanya memiliki kesamaan dari segi niat yakni memohon pengampunan atas perbuatan dosa, sehingga jasmani dan rohani seseorang kembali bersih. Kata kunci: Pengampunan dosa; Islam; Hindu; wudhu’; mandi di Sungai Gangga